SISTEM PENGELOLAAN KEARSIPAN GOOGLE MELALUI BIG DATA: Array - Aldha Shafrielda Sihab; Anugerah Pagiyan Nurfajar (Arsip Nasional Republik Indonesia, 2020)
This article examines the use of Big Data technology for the records and archives administration system in the contemporary era. Big Data can be defined as a collection of data that is extremely large and complex which cannot be dealt with the traditional data processing software. This technology makes it possible to store large amounts of data and can be accessed quickly. By implication, Big Data served sufficiently as a digital records and archives administration system. One of companies in the world that uses Big Data as a digital system is Google. Inc. This phenomenon is quite new in the contemporary era, hence it is quite interesting to see